FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN WARGA TERHADAP PROTOKOL KESEHATAN PADA ERA ADAPTASI KEBIASAAN BARU DI RW 006 KELURAHAN ABADIJAYA TAHUN 2021 - Nadia Fauzana (2022)
The era of new normal is time when people's activities have started to return normal before the Covid-19 pandemic. Therefore, the implementation of health protocols must to be improved, so that the incidence and death rates can be controlled. The purpose of this study was to identify factors related to citizen compliance of health protocols in the era of new normal in RW 006 Kelurahan Abadijaya 2021. This study used a quantitative method through cross-sectional, with cluster random sampling technique. The number of samples are 281 people. The instrument is a questionnaire sheet. The results showed most of the respondents did not comply with the health protocol (52%). Based on chi-square test analysis results, the factors that have significant relationship with adherence of health protocol are gender (p = 0.046), education (p = 0.016), knowledge (p = 0.006), belief (p = 0.000), facilities (p = 0.000), government support (p = 0.000), and health workers support (p = 0.000). Based on multivariate analysis results, belief is the most influential factors on the health protocol compliance (POR = 9,7; 95% CI 5,01 - 18,76). Therefore, it is hoped that the residents of RW 006 Kelurahan Abadijaya can improve their compliance with health protocols.